Adult and continuing education in Malaysia - Muhamad, Mazanah (Universiti Putra Malaysia Press, 2001)
Co-published by Unesco and Universiti Putra Malaysia, this study based on extensive research explores adult and continuing education (ACE) in Malaysia. It looks at the history and context of ACE, the providers of ACE, the curriculum and the resources of ACE in the country. Three further chapters focus on what adults learn, the teaching methods used, and the challenges of providing ACE in the future.